El impacto del género, el nivel socioeconómico y la escuela en las destrezas de español de los estudiantes puertorriqueños - Morales-Reyes, Alexandra; Pérez Vargas, José C.; Rolke, Wolfgang; Siberón, Jessimar (Borealis – An International Journal of Hispanic Linguistics, 2022)
Studies that look at language teaching and learning in Puerto Rico are mainly focused on the effects that macrolevel factors (e.g., political status and language policies) have on Puerto Ricans’ linguistic competence. These factors have been linked to low language proficiency in students of the public school system. However, the impact of microlevel factors (e.g., gender, SES, and school) have been practically overlooked. The present study aims to address this gap by evaluating the effects of gender, socioeconomic status, and school on students’ Spanish skills. We used data from the Medición y Evaluación para la Transformación Educativa (META). The total sample size was 21,425 11th grade students from 194 public schools. Statistical analyzes reveal a linguistic gap by gender and socioeconomic status. In addition, they suggest that the effectiveness of the school and the composition of the school population have a mitigating function in the gender and SES gap. We propose that, although the school, in some cases, does seem to fulfill a compensatory function, the effectiveness of the school seems to be closely linked to the socioeconomic conditions of its students. Keywords: gender; socioconomic status; school; linguistic performance; students; academic gaps